PENGARUH PUPUK HAYATI MIKORIZA DAN TUMPANGSARI DENGAN KEDELAI TERHADAP PERTUMBUHAN DAN HASIL DUA GALUR PADI BERAS HITAM SISTEM IRIGASI AEROBIK: Kata kunci: Padi beras hitam, galur harapan, tumpangsari, kedelai, mikoriza. - Wayan Wangiyana; I Ketut Ngawit; Maesarah Maesarah (Innofarm:Jurnal Inovasi Pertanian, 2022)
Abstract. Black rice is a functional food ingredient that is very beneficial for human health, but in general, black rice varieties are mostly upland rice with low productivity. This study aimed to determine the effect of mycorrhiza biofertilizer and intercropping with soybean on growth and yield of two promising lines of black rice in an aerobic irrigation system. The experiment was carried out in Dasan Tebu, Kediri, West Lombok, from May to September 2020, which was arranged according to the Split Split-Plot design with three blocks and three treatment factors, namely black rice genotypes (G3; G9) as the main plots, intercropping with soybeans (T0: without intercropping; T1: with intercropping) as the sub-plots, and mycorrhiza biofertilizer application (M0: without; M1: with mycorrhiza) as the sub-sub-plots. The results indicated that both black rice genotypes were different only in the percentage of unfilled grains, i.e. lower in G3 (10.43%) than in G9 (14.39%). Additive intercropping with soybean significantly increased growth and yield components of black rice, with a higher grain yield was on black rice intercropped with soybeans (38.42 g/clump) compared to monocrop rice (32.62 g/clump). Application of mycorrhiza biofertilizers also significantly increased tiller number, dry straw weight, and grain yield per clump, and decreased the percentage of unfilled grains, with a higher grain yield was obtained in black rice supplied with mycorrhiza biofertilizer (38.47 g/clump) than without mycorrhiza (32.57 g/clump). However, there were significant interactions between the treatment factors, especially on grain yield, indicating that G9 was more responsive to application of mycorrhiza biofertilizer than G3.